Gestational trophoblastic neoplasia: a meta-analysis evaluating reproductive and obstetrical outcomes after administration of chemotherapy. Issue 6 (July 2019) - Tranoulis, Anastasios; Georgiou, Dimitra; Sayasneh, Ahmad; Tidy, John
Abstract : Introduction: Gestational trophoblastic neoplasia represents a rare placental malignancy spectrum that is treated with single- or multi-agent chemotherapy. This disease often impacts women of childbearing age, making post-chemotherapy fertility and obstetrical outcomes an important consideration. We aimed to ascertain the pregnancy rates and obstetric outcomes in women with gestational trophoblastic neoplasia after undergoing treatment with chemotherapy. Methods: A systematic literature review was conducted to identify studies that reported post-chemotherapy fertility and obstetric outcomes among women with gestational trophoblastic neoplasia. We performed a single-proportion meta-analysis for the outcomes of conception/pregnancy rate, term live birth rate, first and second trimester spontaneous abortions rate, stillbirth rate, premature delivery rate, and fetal/neonatal malformation rate. Results: A total of 27 studies were included in the analysis. The median age ranged between 25.5 and 33.1 years. The pregnancy rate among women with a desire to conceive, comprising a total of 1329 women and 1192 pregnancies, was 86.7% (95% CI 80.8% to 91.6%). The term live birth rate in 6752 pregnancies was 75.84% (95% CI 73.4% to 78.2%). The adverse pregnancy outcomes were seemingly comparable to those of the general population apart from a minor increase in the stillbirth rate. The pooled proportion for the outcome of malformation rate was 1.76% (95% CI 1.3% to 2.2%). The repeat mole rate in 6384 pregnancies was 1.28% (95% CI 0.95% to 1.66%). Subsequent sub-group analysis indicated that neither multi-agent chemotherapy nor conception within 12 months post-chemotherapy increased the adverse obstetric events risk or fetal malformations. Conclusions: Nearly 90% of patients desiring future fertility after chemotherapy for gestational trophoblastic disease were able to conceive. In addition, adverse pregnancy outcomes were similar to that in the general population. Multi-agent chemotherapy does not seemingly increase the malformation rate.